Pengaruh Variasi Konsentrasi dan Debit Pada Pengolahan Air Artificial (Campuran Grey Water dan Black Water) Menggunakan Reaktor UASB - Fauzia Rahmiyati Yazid (Jurnal Teknik Lingkungan, 2012)
In this studyMixture of domestic grey water and black water were investigated. This Mixture consists of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), and Nitrate (NO3). This research investigated the influence of concentration and flow variation parameters to treating the Mixture Grey Water and Black Water. Effluent quality of decreasing concentration varied by the concentration and flow recorded BOD was about102-544 mg/l, COD was about287-1.230 mg/l,TSS was about 280-780 mg/l and For treating  nitrate the result was fair enough than others was about 4-12 mg/l. According to the flow variation resulted the retention time are4, 6and 8hours. The best effluent quality was happened878 mg/LCOD, and varied by flow are 0,125. The results of research showedthe higher concentration will decrease the value of BOD and Nitrate removal, due to the influence of pH.The higher flow will decrease the value of BOD and increase COD, TSS, and Nitrate removal, and  optimum condition ensued ata debit of0,125 l/hour.